Strategi Komunikasi Digital Berbasis Copywriting dalam Penguatan Citra Merek Perusahaan Teknologi Kesehatan Trustmedis - Rizqiyono, M. Fahmi; Sugito, Sugito (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
The development of digital communication has encouraged companies to adapt in order to build public image and trust through more effective and valuable communication strategies. PT Inovasi Teknologi Solusindo (Trustmedis), which provides health technology based on the Electronic Medical Record (EMR) system, uses a digital communication strategy in the form of copywriting to strengthen its brand image as one that is trustworthy, informative, and empathetic. This study uses a descriptive qualitative method by analyzing Trustmedis' digital content on Instagram, Facebook, and YouTube platforms, as well as data on audience performance from Meta Business Suite. The analysis was conducted using the AIDA (Attention, Interest, Desire, Action) model to determine the extent to which persuasive messages are able to build emotional connections and encourage action from the audience. The results show that the application of copywriting principles successfully increased audience engagement through consistent, empathetic, and contextually appropriate messages. Empirical data showed a significant increase in interaction indicators (377.5%), link clicks (288%), reach (66.8%), and views (67.7%), demonstrating the success of Trustmedis' digital communication strategy. Theoretically, this research provides further insight into digital communication in the field of health technology, emphasizing that copywriting is not only a promotional tool but also a way to establish public value and trust in building a sustainable digital brand image.